Chemical systematics of Neotropical termite genera with symmetrically snapping soldiers (Termitidae: Termitinae). Issue 1 (5th May 2017) - Kyjaková, Pavlína; Roy, Virginie; Jirošová, Anna; Krasulová, Jana; Dolejšová, Klára; Křivánek, Jan; Hadravová, Romana; Rybáček, Jiří; Pohl, Radek; Roisin, Yves; Sillam-Dussès, David; Hanus, Robert
Abstract: Termite soldiers often combine mechanical adaptations with defensive chemicals secreted from the frontal gland. Amongst the most remarkable strategies for mechanical defence, symmetrical and asymmetrical snapping mandibles evolved in several lineages of the diversified subfamily Termitinae (Termitidae). The contribution of the frontal chemical weapon to defence in snapping soldiers has long been doubted and the subfamily Termitinae overlooked with respect to soldier-produced chemicals. We recently reported an active frontal gland secreting unique defensive chemicals in the symmetrically snapping soldiers of Cavitermes tuberosus . The aim of the present study was a larger-scale comparison of chemical defence in symmetrically snapping soldiers. We studied the anatomy of the frontal gland and the chemistry of its secretion in five additional Neotropical species and mapped our observations on a de novo constructed molecular phylogeny of the target group. We show that the soldiers of all studied species possess a functional frontal gland, housed in part in the frontal projections on their heads. Phylogenetic reconstruction groups the studied taxa into two well-defined clades, supported by fundamental differences in defensive chemicals, either arising exclusively from the lipogenic pathway or containing also the products of the isoprenoid pathway. Our results also identify a new genus of symmetrical snappers, related to the genus Cavitermes, incorrectly classified in several previous studies.